Adiponectin Improves In Vitro Development of Cloned Porcine Embryos by Reducing Endoplasmic Reticulum Stress and Apoptosis - Muhammad Rosyid Ridlo (Animals, 2021)
The main factor of embryonic demise is endoplasmic reticulum (ER) stress. Successful attenuation of ER stress results in an improvement in embryo development. We studied the impact of adiponectin in the in vitro culture (IVC) of porcine embryos derived from parthenogenetic activation and somatic cell nuclear transfer (SCNT). The first experiment revealed that 15 and 30 μg/mL adiponectin treatments improved cleavage, blastocyst rates, and total cell number (TCN) of parthenogenetic embryos and reduced the expression of XBP1 compared to the 5 μg/mL adiponectin treatment and control groups (p < 0.05). The second experiment showed that cleavage rate, blastocyst formation rate, and TCN of blastocysts were improved in the 15 μg/mL adiponectin treatment group compared with the control group, with significantly reduced XBP1 expression in ≥4-cell stage SCNT embryos and blastocysts (p < 0.05). Treatment with 15 μg/mL adiponectin significantly improved the expression of XBP1 and reduced the expression of ER stress-related genes (uXBP1, sXBP1, PTPN1, and ATF4), increased the expression levels of pluripotency-related genes (Nanog and SOX2), and decreased apoptosis-related gene expression (Caspase-3). These results suggest that 15 μg/mL adiponectin enhanced the in vitro developmental capacity of early-stage SCNT porcine embryos by reducing ER stress and apoptosis.